Inhibition of α-amylase by polyphenolic compounds: Substrate digestion, binding interactions and nutritional intervention. (October 2020) - Sun, Lijun; Wang, Yueyi; Miao, Ming
Abstract: Background: α-Amylase is a key enzyme of starch digestion, playing an important role in deciding glucose releasing amount. Inhibition of the enzyme activity by polyphenols is suggested as a potential approach in controlling starch digestion and regulating postprandial hyperglycaemia. Scope and approach: α-Amylase inhibition by polyphenols results from polyphenol-enzyme binding interactions that have been characterized by inhibition kinetics, spectroscopy and thermodynamic analyses. To further elucidate the inhibition mechanism, making the inhibition visible, studies regarding biochemical, biophysical and molecular mechanisms are summarized. Key findings and conclusions: Macroscopically, α-amylase inhibition causes retarded digestion of starchy substrates, visible from the production reaction color or fluorescence. Microscopically, detail inhibition kinetics reveals the inhibition types and theoretic interacting sites. X-ray diffraction (XRD) is powerful in extracting the binding modes (detail amino acid residues, polyphenol moieties and interaction forces involved in polyphenol-amylase interactions). Through polyphenol-amylase binding analysis by XRD and NOE correlation of polyphenol atoms by rotating-frame Overhauser enhancement spectroscopy (ROESY)-NMR, the contribution of intramolecular interactions between polyphenol ring-groups to the binding is evaluated. The key phenolic moieties for binding are also obtained by saturation transfer difference (STD)-NMR and/or molecular docking. Besides, by combing fluorescent properties and thermal stability of α-amylase, the enzyme conformational changes may be obtained. Additionally, following delayed starch digestion, α-amylase inhibition is indicated by retarded increase in blood glucose level and colonic fermentation properties of undigested starch. Conclusively, visible characterization helps to understand how a polyphenol develops the inhibitory activity, and to reasonably explore functional factors for alleviation of carbohydrate metabolism disorder. Highlights: Detail inhibition kinetics reveals the inhibition types, constants and binding sites. XRD describes amino acid residues, polyphenol moieties, forces involved in inhibition. STD-NMR and molecular docking indicate phenolic moieties in polyphenol-enzyme binding. FQ and DSC characterize conformational changes of α-amylase by polyphenol binding. Amylase inhibition may be indicated by blood glucose level and microbial fermentation.